2003
DOI: 10.1177/000331970305400301
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Coronary Artery Disease, Risk Factors and Intima-Media Thickness of Carotid Artery, Arterial Distensibility, and Stiffness Index

Abstract: Atherosclerosis is a diffuse process that involves vessel structures. In recent years, the relation of noninvasive parameters such as intima-media thickening (IMT), arterial distensibility (AD), and stiffness index (SI) to cardiovascular diseases has been researched. However, we have not found any study that has included all these parameters. The aim of this study is to examine the relation between the presence of coronary artery disease (CAD) and its risk factors to AD, SI, and IMT, which are the noninvasive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 33 publications
2
42
0
2
Order By: Relevance
“…Hirai et al first demonstrated that stiffness parameter of CA and aorta increased with the number of stenoses of coronary arteries as determined by CAG 17) . Alan et al found that IMT and stiffness parameter in the CAD group were higher than those in the control group, and that the sensitivity, specificity, and positive predictive and negative predictive val- ues of IMT for angiographic CAD diagnosis were 70%, 75%, 77%, and 66%, respectively 18) . In elderly men, stiffness parameter was also found to be a significant predictor of cardiovascular mortality (HR, 1.68) during 48-month follow-up 19) .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hirai et al first demonstrated that stiffness parameter of CA and aorta increased with the number of stenoses of coronary arteries as determined by CAG 17) . Alan et al found that IMT and stiffness parameter in the CAD group were higher than those in the control group, and that the sensitivity, specificity, and positive predictive and negative predictive val- ues of IMT for angiographic CAD diagnosis were 70%, 75%, 77%, and 66%, respectively 18) . In elderly men, stiffness parameter was also found to be a significant predictor of cardiovascular mortality (HR, 1.68) during 48-month follow-up 19) .…”
Section: Discussionmentioning
confidence: 98%
“…Stiffness parameter is unique among these indices since it features correction for the ratio of systolic and diastolic blood pressures and minimal effects of acute changes in blood pressure 16,17) . Increased stiffness parameter of the carotid artery and/or aorta has been reported to be associated with CAD 15,[17][18][19] . We have also demonstrated that stiffness parameter is increased in diabetic patients with chronic kidney disease 20) , latent symptoms of peripheral artery disease 21) , insulin resistance 22,23) , and hypoadiponectinemia 24) .…”
Section: Introductionmentioning
confidence: 99%
“…2 Arterial stiffness has been consistently proven to be a predictor of adverse cardiovascular outcomes. 3 Stiffness index b is a measure of carotid arterial stiffness that is associated with coronary atherosclerosis 4,5 and vascular dysfunction 6 in patients with glucose intolerance and insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial stiffness increases with advancing age [7], and is as an emerging biomarker in the assessment of vascular health [40]. Large arterial stiffness is associated with an increased risk for coronary heart disease [8], hypertension [9], left ventricular hypertrophy, diastolic dysfunction [10,11] and all-cause mortality [12]. However, although aerobic exercise effectively decreases arterial stiffness, it does not induce gains in strength and lean body mass, as well as increases in bone density compared with resistance training [4,41].…”
Section: Discussionmentioning
confidence: 99%
“…Also, arteries lose their compliance with advancing age, independent of atherosclerosis, hypertension and other disease states [7]. This age-related reduction in central arterial compliance is associated with an increased risk for coronary heart disease [8], hypertension [9], left ventricular hypertrophy, diastolic dysfunction [10,11] and all-cause mortality [12].…”
mentioning
confidence: 99%